Entre o imaginar e o agir: possibilidades para construção de conhecimento em ciências nos anos finais do ensino fundamental - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This study tried to create conditions for planning and acting more dynamic and creative in Teaching of Sciences. As a demand for this process, we elaborated a propitious environment to construct knowledge and apply it to absolving classes in the elementary school, “Ensino Fundamental” - according to the Brazilian education system. The objective of this work was to explore the ninth level of the education program, by means of a methodology that could enable passing through bifurcated ways of information, so that students could organize it and transform it into new acquired knowledge. In order to support the purpose of this project and perform this research in a qualitative and investigative way, we referred to texts written by Edgar Morin, Saturnino de La Torre, Rita de Cássia Souza and Virgínia Kastrup. In this cottage, formerly used for classes of Environmental Education, students created, according to their imagination, a “Secret Laboratory”. This “Secret Laboratory” worked as an instrument for investigations and during the creation process, the students became “scientists”, and once becoming one, they had to give general explanations of a designed topic and also solve its ongoing problems, as well as undertake experiments, and finally, look for corresponding themes in internet and learning books to improve their reading and writing abilities, what could be reproduced later on in their own diary, the “Diary of a Scientist”. In order to dynamize the interaction teacher-student, we also created a virtual character for the first one, named “the kindly grandma, just met on the bus”, whose main task was to send messages, materials, samples or new missions, via internet or conventional mail, to the students, the “scientists”, to be investigated and subsequently solved. Creating characters, that are able to interact the traditional fixed positions between teacher and student, as well as it pre-stablished functions on impartation/reception of knowledge, announces hereto the prerequisites of our figured out methodology, that intends to create some dynamic variances in opposite of hegemonic ways to organize the conventional teaching methods. For data collection we worked issues related to the discipline of Chemistry during two trimesters. These issues were planned based on the normal scholar program in association with the titular teacher of the discipline. During the process of implementation of the proposal, it was possible to create conditions for the action and creation were mainstreamed by imagination. Thus, producing interconnections, dynamic organization of information, provoking new questions, mobilizing the search for other information, which led to new knowledge. In the organization of the information obtained in the course of activities, we realized that occurred situations that mobilized students both to "explain" the problematic situations arising of intervention strategies in the plan of action and creation, as to "imply", in addition to action, or by imagination. We group these situations three times and we will call: explanatory metamorphic moment intermetamórfico time and metamorphic implicative time.
Keywords: Creating; Teaching of sciences; Complexity; CNPQ::CIENCIAS HUMANAS; Imaginar; Ensino de ciências; Complexidade